W6 Cancer, mental health and end of life simulation – a compelling case of the need for integrated learning and faculty development. (5th November 2017) - Fernando, A; Snelgrove, H; Gosling, N
Abstract : Background: This workshop replicates interactive, simulated scenarios and debriefs from an innovative and evidence based inter-professional simulation course aiming to improve healthcare professionals knowledge, confidence and ability in assessing and managing mental health needs for cancer and end of life patients. The rationale is strongly compelling. Mental Health co-morbidity in Cancer and end of life care is very common, poorly recognised and treated, leading to marked distress, loss of functioning and loss of life. In an ageing population, and one with an increasing burden of both cancer and chronic mental illness (1), it is imperative that we foster an integrated approach for inter-professional training in this area to encourage better training at the mental-physical interface. Learning Objectives and Session Description: Improved awareness, knowledge, and confidence in identifying, assessing and managing common mental health co-morbidity in cancer patients and end of life care, appropriate to their professional role, including discussing how to translate these improvements into clinical outcomes and sharing of resources. Equipping and empowering participants to engage in the design, implementation and evaluation of similar inter-professional simulation courses and the opportunity to collaborate across institutions and countries in course, faculty and curriculum development. This will consist of a very brief 'pre-teach snapshot' highlighting the complexities of managing mental health in cancer and end of life care, followed by a live, inter professional, high-fidelity, evidence based scenario targeting co-morbidity, utilising a trained actor and participant volunteers. There will then be a faculty run structured debrief (of participants and observers) concentrating on technical and human factors aspects, before culminating in a discussion about challenges and benefits of setting up similar simulated courses. Target Audience: Any healthcare professionals with an interest or involvement in cancer care, end of life and mental health should attend, including primary care, those with an interest in mental-physical comorbidity, Drs and nurses of all grades, and allied healthcare professionals. The workshop will also be useful for researchers and medical educators, those with an interest in quality improvement and patient safety, simulation and developing similar courses, evaluation, faculty development, inter-professional skills and curriculum development. The workshop can be run effectively with a maximum number of approximately 40 participants; though can be optimally staged with fewer participants.